REDESIGN OF THE MAIN DAM AND DAM BREAK MODELING OF MENINTING DAM, LOMBOK ISLAND - Azis Ghifari, Mochammad
The Meninting River Basin (DAS Meninting) has a high potential for water availability, but the southern part of Lombok Island has limited water availability despite having extensive agricultural land potential. Therefore, the Meninting Dam was constructed to align the potential water availability with the available land on Lombok Island. The Meninting Dam also poses a potential hazard if it experiences a dam failure, given its proximity to the densely populated city of Mataram. Based on hydrological analysis, the main dam is designed with a planned flood discharge of Q1000 and QPMF. The dam structure is planned to have a height of 86 meters and a crest width of 16 meters, with a dead storage elevation of 167 meters, effective storage of 203.5 meters, and a dam crest of 209 meters. Flood modeling due to dam failure using the HEC-RAS. As a result, 20 villages/urban areas are potentially affected by the flood.